Studies on use of sodium poly acrylate (SPA) for low salt animal skinpreservation - Sandhya, K. V.; Brindha, Velappan; Abinandan, Sudharsanam; Vedaraman, N.; John, Sundar V.; Suresha, P. R.; Badiger, Manohar; Chinnaraj, Velappan kandukalpatti; Muralidharan, C. (IULTCS CONGRESS 2017, 2017)
In this study, commercial sodium poly acrylate (SPA) is used along with sodium chloride for low salt skin preservation. SPA is a super-absorbent polymer which can absorb water many times of its own weight.